IDENTIFIKASI KOMODITAS UNGGULAN WILAYAH DALAM PERSPEKTIF PERTANIAN BERKELANJUTAN DI SULAWESI TENGGARA - Zainal Abidin (Universitas Muhammadiyah Kendari, 2018)
Developing of agricultural commodity at Southeast Sulawesi have specific ficture base on natural resources. The research was conducted to know the commodity that have sustainable competitifnes. Research was done using time series data 2010 – 2016 and analize with Location Quotien (LQ) dan Dinamic Location Quotient (DLQ) methode. The result of research show that food commoditeis that have become the sustaibnable bases commodity are corn, peanut and cassava, besides that rice and soybean only can became shor-term bases commodity. Livestock commodities such us sow, goat, native chicken and rusting hens broiler also can became bases commodity for a long time in several regencies. Even that clove, cashew nut, coconut, pepper and cocoa plantation can became the bases of commodities in several regencies such us Buton, Muna, Konawe Selatan, Kolaka Utara, Konawe Utara, Kendari dan Bau-Bau. Horticulture commodities such us chili pepper, zingeber and orange also can became sustainable bases commodities. So developing that commoditeis should be have policy supporting such us kredit regulation, infrasctukture and also aplicatif and simple technologies.